Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0196933
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of functional activity and connectivity by acupuncture in patients with Alzheimer disease as measured by resting-state fMRI

Abstract: Acupuncture has been used in the therapy of Alzheimer disease (AD); however, its neural mechanisms are still unclear. The aim of this study is to examine the effect of acupuncture on the functional connectivity in AD by using resting-state functional magnetic resonance imaging (rs-fMRI). Twenty-eight subjects (14 AD and 14 normal controls) participated in this study. The rs-fMRI data were acquired before and after acupuncture stimulation at the acupoints of Tai chong (Liv3) and Hegu (LI4). During the baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 50 publications
3
72
0
1
Order By: Relevance
“…Notably, findings from several studies were contradictory. For example, some studies have found significantly decreased amplitude of low-frequency fluctuation (ALFF) in parahippocampal gyrus (PHG), superior temporal gyrus (STG) and postcentral gyrus in AD patients (Liu et al, 2014;Cha et al, 2015;Zheng et al, 2018), whereas some have reported increased ALFF in these regions (Wang et al, 2011). Inconsistent results could also be found in studies focus on patients with MCI (Wang et al, 2011;Xi et al, 2012) or amnestic MCI (aMCI;Han et al, 2011;Cai et al, 2017;Pan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, findings from several studies were contradictory. For example, some studies have found significantly decreased amplitude of low-frequency fluctuation (ALFF) in parahippocampal gyrus (PHG), superior temporal gyrus (STG) and postcentral gyrus in AD patients (Liu et al, 2014;Cha et al, 2015;Zheng et al, 2018), whereas some have reported increased ALFF in these regions (Wang et al, 2011). Inconsistent results could also be found in studies focus on patients with MCI (Wang et al, 2011;Xi et al, 2012) or amnestic MCI (aMCI;Han et al, 2011;Cai et al, 2017;Pan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have partially clarified the mechanisms by which acupuncture can prevent AD through anti-inflammatory (Ding et al, 2017), anti-oxidative (Sutalangka et al, 2013), and anti-apoptotic effects (Guo et al, 2015(Guo et al, , 2016. Moreover, acupuncture can modulate the functional activity and connectivity of specific cognition-related areas of the brain in AD patients (Wang et al, 2012Liang et al, 2014;Zheng et al, 2018). However, the effect of manual acupuncture (MA) on CBF in AD therapy and the specifics of its molecular mechanisms are still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, it is becoming more and more popular as a complementary and alternative treatment for brain diseases. Some ndings have showed that it has a de nite therapeutic effect for brain diseases, such as stroke [17,18,19], AD [20,21,22], PD [23,24,25], depression [26,27] etc. For example, Qi Huang et al [28] conducted a meta-analysis and found that acupuncture could improve clinical e cacy rate, Mini-Mental State Examination score, Ability of Daily Living Scale score and Alzheimer's Disease Assessment Scale-Cognition score in AD patients.…”
Section: Figurementioning
confidence: 99%